Monsters in Society : Alterity, Transgression, and the Use of the Past in Medieval Iceland - Merkelbach, Rebecca (Northern medieval world. On the margins of Europe., 2019)
Dragons, giants, and the monsters of learned discourse are rarely encountered in the Sagas of Icelanders, and therefore, the general teratological focus on physical monstrosity yields only limited results when applied to them. This, however, does not equal an absence of monstrosity - it only means that monstrosity is conceived of differently. This book shifts the view of monstrosity from the physical to the social, accounting for the unique social circumstances presented in the Íslendingasögur and demonstrating how closely interwoven the social and the monstrous are in this genre. Employing literary and cultural theory as well as anthropological and historical approaches, it reads the monsters of the Íslendingasögur in their literary and socio-cultural context, demonstrating that they are not distractions from feud and conflict, but that they are in fact an intrinsic part of the genre?s re-imagining of the past for the needs of the present.